Pengaruh Konsumsi Minuman Berkafein terhadap Kualitas Tidur Mahasiswa UIN Sumatera Utara Medan - Khairunnisa, Khairunnisa; Riski Andriani; Wahyudi Wahyudi; Puti Miratil Hayati Efri; Dhea Rizky Fitri Saragi (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Caffeine is the most widely consumed psychoactive substance in the world and is produced in a variety of foods, beverages, and medicines. Understanding the effects of caffeine is essential for health care information and consumption, especially on a person's sleep quality. The quality of sleep in Indonesia represents a significant concern shaped by numerous elements, encompassing technology and individual health. Adverse influences, like the intake of caffeine, play a crucial role in determining inadequate sleep quality. The goal of this research is to examine how the consumption of caffeinated drinks impacts the sleep quality of students at UINSU Medan. Quantitative methodology was employed, utilizing a cross-sectional research design. Participants were selected through a simple random sampling method. In total, this research collected data from 150 students. Primary data were gathered via questionnaire. The results of this study show that there is an influence but not significant between the consumption of caffeinated beverages and sleep quality in UINSU Medan students which can be seen from the results of the Chi-Square test obtained a value of p=0.624 (p>0.05), meaning that at alpha 5% it shows that there is no strong influence between the two variables. This is likely influenced by individual factors such as genetic sensitivity to caffeine. In contrast, sleep duration was shown to have a significant influence on sleep quality (P value 0.001), where less sleep duration was associated with poor sleep quality.